Adapting Aid Allocation Criteria to Development Goals - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2008)
This paper analyzes aid allocation from a normative point of view. It attempts to design aid allocation criteria adapted to development goals and combining the principles of effectiveness and equity in a transparent and integrated framework. The common view about aid selectivity, which essentially refers to the quality of governance and policy indicators, is challenged for several reasons, in particular the weakness of the relationship between these indicators and aid effectiveness and the risk of countries facing exogeneous difficulties being left behind. Consistent with the lessons of the literature on aid effectiveness, new criteria for aid allocation are proposed, in particular that of structural vulnerability which has been shown to increase the marginal effectiveness of aid, because aid dampens its negative effects.Egalement disponible sur le site de UN ECOSOC.
Keywords: F35; O19; 330